DESIGN OF CAPABILITY ASSESSMENT MODEL FOR AN INFORMATION SECURITY (ISO 27005) AND ANTI-BRIBERY (ISO 37001) RISK MANAGEMENT USING 33020 (Study on Supply Chain Management) - Okvita Dewi, Titi
The term risk management is made to describe an approach where the level of security of a company's information resources is compared to the risks it faces. Information security risk management (MRKI) that is applied to organizations can refer to many international standards that deal with MRKI governance, such as ISO 27005, 31000, NIST SP 800-300, NIST SP 800-39 and Octave Framework. In this thesis, the MRKI framework that will be used is ISO 27005. The same framework will be used in Anti-Bribery Risk Management (MRAP).